Innovation partnership for a roadmap on vaccines in Europe (IPROVE): a vision for the vaccines of tomorrow - Medaglini, Donata; De Azero, Magdalena R.; Leroy, Odile; Bietrix, Florence; Denoel, Philippe (Vaccine, 2018)
A clear vision for vaccines research and development (R&D) is needed if Europe is to continue to lead the discovery of next generation vaccines. Innovation Partnership for a Roadmap on Vaccines in Europe (IPROVE) is a collaboration between leading vaccine experts to develop a roadmap setting out how Europe can best invest in the science and technology essential for vaccines innovation. This FP7 project, started in December 2013, brought together more than 130 key public and private stakeholders from academia, public health institutes, regulators, industry and small and medium-sized enterprises to determine and prioritise the gaps and challenges to be addressed to bolster innovation in vaccines and vaccination in Europe. The IPROVE consultation process was structured around seven themes: vaccine R&D, manufacturing and quality control, infrastructure, therapeutic vaccines, needs of small and medium-sized enterprises, vaccines acceptance and training needs. More than 80 recommendations were made by the consultation groups, mainly focused on the need for a multidisciplinary research approach to stimulate innovation, accelerated translation of scientific knowledge into technological innovation, and fostering of real collaboration within the European vaccine ecosystem. The consultation also reinforced the fact that vaccines are only as good as their vaccine implementation programmes, and that more must be done to understand and address vaccination hesitancy of both the general public and healthcare professionals. Bringing together a wide range of stakeholders to work on the IPROVE roadmap has increased mutual understanding of their different perspectives, needs and priorities. IPROVE is a first attempt to develop such a comprehensive view of the vaccine sector. This prioritisation effort, aims to help policy-makers and funders identify those vaccine-related areas and technologies where key investment is needed for short and medium-long term success.